Association between Modifiable Risk Factors and Arterial Hypertension in Adolescents from Moa - Alexander Torres Molina (Revista Finlay)
Foundation: high blood pressure in adolescents is statistically related to modifiable risk factors that influence the onset and evolution of the disease. Objective: measure the degree of association between modifiable risk factors and blood pressure levels in adolescents from Moa, Holguín. Methods: an observational, prospective longitudinal cross-sectional study was carried out in the period between September-December 2022. The universe consisted of 1,561 adolescents aged 15-19 years and the sample was 524 (33.56 %). A systematic probabilistic sampling was carried out. The following variables were analyzed: body mass index, abdominal circumference index, night sleep, hours of sedentary activity and weekly frequency of junk food. Statisticians were used: absolute frequency and percentage and statistical tests; Chi square. Results: 34.88 % of adolescents with BMI>97 pp were hypertensive and 37.21 % were prehypertensive, X2p=167.1976 > X2c=20.0902, (VC=0.3646). 40.00 % of those with ICA>97pp were diagnosed with HTN and 40.00 % with prehypertension, X2p=239.6183 > X2c=20.0902, Cramer's V (VC= 0.4366). 14.14 % of those who slept 6 hours or less were stratified as hypertensive, X2p=54.1834 > X2c=13.2767 (VC= 0.2076). Adolescents who spent more than six hours a day in sedentary activities (10.63%) suffered from hypertension and prehypertension (11.88 %), X2p=14.1081> X2c=13.2767 (VC= 0.1059). 14.22 % ate junk food with a frequency equal to or greater than six times a week and were hypertensive, X2p=29.8662 > X2c=13.2767 (VC= 0.1541). Conclusions: there was a moderate association between body mass index, abdominal circumference index and blood pressure. The association between hours of night sleep, daily hours of sedentary activity and weekly frequency of junk food with blood pressure figures.